Analysis of Product Quality and Service Quality Towards Customer Loyalty Mediated by Customer Satisfaction at Wanaku Chinese Restaurant in Jimbaran Badung Regency - I Nyoman Agus SETYAWAN; Gusti Ayu SUGIATI; Putu Ngurah Suyatna YASA (International Journal of Environmental, Sustainability, and Social Science, 2025)
This study was conducted at Wanaku Chinese Restaurant to analyze the effect of product quality on and service quality on customer loyalty mediated by customer satisfaction. The sample was determined through purposive sampling, so that 100 customers who had made purchases at Wanaku Chinese Restaurant were obtained. Data were collected through a questionnaire with Likert scale measurements, then analyzed using instrument tests, SEM-PLS, and hypothesis tests. The results show that product quality has a positive and significant effect on customer satisfaction and loyalty, service quality has a positive and significant effect on customer satisfaction and loyalty, customer satisfaction has a positive and significant effect on customer loyalty, customer satisfaction mediates the effect of product quality on customer loyalty, and customer satisfaction mediates the effect of service quality on customer loyalty.